COHORT PROFILE: The Complications of Long‑Term Antiretroviral Therapy study in Uganda (CoLTART), a prospective clinical cohort - Mayanja, Billy Nsubuga; Kasamba, Ivan; Namakoola, Ivan; Kazooba, Patrick; Kaleebu, Pontiano; Munderi, Paula (AIDS research and therapy, 2017)
Antiretroviral therapy (ART) improves the survival and quality of life of HIV-positive individuals, but the effects of long-term ART use do eventually manifest. The Complications of Long-Term Antiretroviral Therapy cohort study in Uganda (CoLTART) was established to investigate the metabolic and renal complications of long-term ART use among Ugandan adults. We describe the CoLTART study set-up, aims, objectives, study methods, and also report some preliminary cross–sectional study enrolment metabolic and renal complications data analysis results.